Response of East African highland bananas to black Sigatoka and Cladosporium leaf speckle under tropical humid forest lowland conditions in West Africa - Pasberg-Gauhl, C.; Gauhl, F. (2000)
The responses of 19 East African highland (EAH) banana cultivars (AAA and AA genomes) and two reference cultivars to black sigatoka (Mycosphaerella fijiensis Morelet) and Cladosporium leaf speckle (Cladosporium musae Mason) were studied in 1993 at Onne (southeastern Nigeria) under ecological conditions of the tropical humid forest lowlands. Plants were evaluated before flowering during the rainy season when conditions were favorable for both plant growth and disease development. Disease development time was found to be the most useful variable to evaluate and distinguish the response of different Musa cultivars to black sigatoka. Black sigatoka symptoms developed on all cultivars observed into the final stage of leaf spots with dry centers, hence none was classified as resistant. On the susceptible reference cultivars 'Valery' (AAA dessert banana) and 'Agbagba' (AAB False Horn plantain) the final symptom stage of black sigatoka developed within 32 days. Sixteen of the EAH banana cultivars expressed a lower level of partial resistance with disease development times ranging from 52 to 65 days. Four EAH banana cultivars expressed a higher level of partial resistance with a disease development time longer than 65 days. A preliminary grouping was also carried out for the host response to C. musae. Two groups with different levels of host response were identified.